2011
DOI: 10.1093/geronb/gbq071
|View full text |Cite
|
Sign up to set email alerts
|

Life-span Socioeconomic Trajectory, Nativity, and Cognitive Aging in Mexican Americans: The Sacramento Area Latino Study on Aging

Abstract: Heterogeneity of cognitive aging among diverse race/ethnic groups may be influenced by intergenerational changes in SES, cultural norms, and behaviors and changes in health related to changes in the social and physical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 21 publications
4
81
1
Order By: Relevance
“…For instance, the impact of SEP on cognition has been linked to its influence on attaining peak performance in midlife, which may affect the timing and trajectory of subsequent declines in later life (10). Further complicating the picture, some have found that slower cognitive decline in later life has been associated with upward mobility in SEP (9), although such an association with diet has been shown to require consistently high diet quality starting at least from midlife (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the impact of SEP on cognition has been linked to its influence on attaining peak performance in midlife, which may affect the timing and trajectory of subsequent declines in later life (10). Further complicating the picture, some have found that slower cognitive decline in later life has been associated with upward mobility in SEP (9), although such an association with diet has been shown to require consistently high diet quality starting at least from midlife (44).…”
Section: Discussionmentioning
confidence: 99%
“…Because the 3MS provides a single measure of global cognition, we could not examine whether the observed associations were restricted to specific cognitive domains. Although we used multiple indicators reflecting both psychosocial and material dimensions of SEP, it could be useful to study additional indicators across the life course (i.e., wealth, household conditions, parental SEP) because upward mobility in SEP has been shown to impact cognition (9). Differences between the analyzed and unanalyzed participants in income and education may have resulted in overestimated and underestimated associations of the prudent and Western patterns, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large number of studies on psychosocial factors and their impacts on the performance of children of different ages in cognitive tasks, most of them use IQ or academic achievement measures (Forns et al 2012;Haan et al 2011). In the present study, neuropsychological variables were added to traditional IQ evaluation, following recent studies that assess neuropsychological functions separately (Noble and Farah 2013;Raizada and Kishiyama 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sattler et al [12] have shown, in 321 elderly participants from the Interdisciplinary Longitudinal Study on Adult Development and Aging followed up for 12 years, that high socioeconomic status measured by monthly household income reduced the risk of developing cognitive impairment by 69% in comparison to subjects with low socioeconomic status. Other studies have used occupation [13], both occupation and education [14], or occupation, education and income [15,16] to assess socioeconomic status. All showed a significant association with dementia or cognitive decline.…”
Section: Introductionmentioning
confidence: 99%